Improving adaptive response to negative stimuli through non-emotional working memory training - Long, Quanshan; Yu, Linlin; Tang, Yancheng; Li, Qing; Hu, Na; Gu, Yan; Chen, Antao (Frontiers in Behavioral Neuroscience, 2023)
People with high working memory (WM) capacity tend to respond proactively and experience a decrease in undesired emotions, implying the potential influence of WM training on emotional responses. Although training emotional WM could enhance emotional control, the training also improves emotional response itself. Thus, the far-transfer effects of non-emotional WM training on emotional responses remain an open question. In the present study, three experiments were conducted to detect these effects. The Preliminary experiment matched the expectations of the gains of the training tasks between the experimental and active control groups (n = 33). In Experiments 1 and 2, participants performed 7-day and 15-day training procedures, respectively. Results indicated that after a 7-day training, non-emotional WM training (n = 17) marginally reduced individuals’ emotional responses compared with the active control group (n = 18); importantly, this improvement became significant after a 15-day training (n(WM training) = 20, n(active control) = 18). A combination analysis for Experiments 1 and 2 showed that training gains on WM performance were significantly related to reduced emotional responses (r = -0.359), indicating a dosage effect. Therefore, non-emotional WM training provides a safe and effective way to enhance adaptive emotional responses.